Meningkatkan Produktivitas dan Sumber Daya Manusia Melalui Kegiatan KKN Tematik - Sutedi, Ade; Setiawan, Rizal; Rahadiansyah, Ardian Tri; Rosmawati, Rosmawati; Hestiyanti, Mita; Amalia, Aceu Emil; Nurbayinah, Siti Rahmah; Maulana, Ilham Ahmad; Rizqulloh, Zidan Rakan; Aulia, Wafa Ghaida; Santika, Sesti; Putra, Andre Pratama; Saputra, Deni; Ilyasa, Muhamad; Dahman, Muhammad; Fathori, Moch Zain; Nurfikri, Muhammad Ikhsan; Pratama, Aldy Gumelar; Hakim, Arif Lukmanul; Fhadillah, Shelly Umayah (Jurnal PkM MIFTEK, 2022)
THEMATIC KKN is an activity with a background in community service. This service is of course aligned with the background of the community in the area where the KKN is carried out. The background of the community in the KKN area of ”‹”‹Wanajaya village Most of the population are MSME managers, breeders and laborers. With this data, an increase in productivity in their business activities is an important thing to explore. Then the increase in productivity must be accompanied by an increase in human resources which basically in this day and age must be able to operate technology that contains information and be able to communicate it properly. In this way, the work program carried out aims to improve business capabilities with qualified human resources. The program is carried out in 4 stages, namely the observation stage, the socialization stage, the implementation stage and the evaluation stage. In the socialization stage it produces data on human resources who have experienced an increase in digital knowledge of 435 people and the evaluation stage produces an effect of increasing community productivity in processing a product in the form of BOKASI fertilizer.